Pseudomonas intra-genus competition determines the protective function of synthetic bacterial communities in Arabidopsis thaliana. - Anton Amrhein; Mingxiao Zhang; Stéphane Hacquard; Anna Heintz-Buschart; Kathrin Wippel (PLoS Biology)
The plant root microbiota is crucial for nutrient acquisition, development, and disease suppression. Although commensal bacteria display host preference, their beneficial impact on their cognate host and mechanisms of species selection by the plant are still unclear. We use bacterial culture collections derived from the two model species Arabidopsis thaliana (At) and Lotus japonicus (Lj) to design synthetic communities (SynComs) and test their protective function upon exposure of At Col-0 to the detrimental root-colonizing At-derived Pseudomonas isolate R401. Lj-derived SynComs were fully protective, whereas At-derived SynComs displayed full protective activity only towards a R401 mutant impaired in the production of inhibitory exometabolites. The protective phenotypes were associated with a reduced titer of the R401 opportunistic pathogen. In vitro antagonist assays, in planta and in vitro bacterial community profiling, as well as strain-swapping and strain-dropout experiments revealed that competition among commensal Pseudomonas strains and R401 determines the success of the opportunist, independent of the original host or the phylogeny of the commensals. Furthermore, we determine the carbon utilization potential of these isolates, which may explain the competition with the detrimental strain and the role of host-secreted compounds. Our results provide evidence that intra-genus interactions within SynComs modulate plant health and disease, and that an individual beneficial strain can be sufficient to outcompete an opportunistic relative. This has implications for the successful development of beneficial microbial consortia for agriculture.